2006
DOI: 10.3892/or.15.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Loss of imprinting in IGF2 in colorectal carcinoma assessed by microdissection

Abstract: Abstract.To ascertain the implications of loss of imprinting (LOI) of the insulin-like growth factor II gene (IGF2) for carcinogenesis, the precise frequency of LOI in colorectal carcinoma was examined using a laser capture microdissection method, and compared to the matched normal colorectal mucosa. LOI was examined by PCR-restriction fragment length polymorphism in combination with direct sequencing. The status was assigned as imprinting when PCR-RFLP showed only one band or sequence with a single peak, othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…In support of our finding, other investigators have recently reported a high percentage of LOI in CRCs (54%) using laser microdissection [47]. Contamination of the tumor tissues with normal cells may result in underestimation of the percentage of LOI.…”
Section: Discussionsupporting
confidence: 75%
“…In support of our finding, other investigators have recently reported a high percentage of LOI in CRCs (54%) using laser microdissection [47]. Contamination of the tumor tissues with normal cells may result in underestimation of the percentage of LOI.…”
Section: Discussionsupporting
confidence: 75%
“…Our technique, which has been modified from previous approaches [10], [11], provides a generalizable strategy for identifying cell class-specific imprinted genes. Such studies can help bring resolution to the important debate about the number and identity of imprinted genes in the brain [7][9].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, positive staining for IGF‐II correlates with increased tumor progression, increased proliferating cell nuclear antigen staining, and decreased patient survival in colorectal cancers (Wang et al . 2005; Maenaka et al . 2006).…”
Section: Discussionmentioning
confidence: 99%